Language for development through drama and theatre in Zimbabwe: an African perspective - Matiza, Vimbai M. (University of South Africa, 2022)
This study discusses the African perspective of the role of language in explaining development issues through the medium of drama and theatre in Zimbabwe. The problem of the study is centred on the idea that development was hardly measured through art. The researcher argues that language used in drama and theatre as a form of art can also contribute to development in Zimbabwe. This development can be witnessed through people’s changing lifestyles, acknowledging the importance of their mother tongue in communication and restoring hope in situations characterised by hopelessness and despair. Descriptive research design was used in the study because it allowed the researcher to dig much deeper into the subject. Data from respondents was gathered through the use of questionnaires, interviews and content/textual analysis of some scripts. In interrogating the issues of development through language in drama and theatre, the research was guided by the African Renaissance theory, Theatre for development and Hymes’ SPEAKING model. As a result, the study observes that language, a people’s indigenous language should be placed at the centre of a performance if that message being conveyed is to change or develop them. The key respondents to the study bring out the idea that there is no language which is superior to the other and the choice of language to be used in a work of art should be determined by the circumstances that prevail. Even the language which is used by the smallest population of people should be given space to flourish and be used by its people. Another major finding of the research is that language itself cannot change people but people change themselves through the use of a language that they understand. This calls for the initiative by the indigenous people and the powers that be to make sure that they use their language at different levels so that all facets of development can be witnessed within their lives. In the final analysis, the researcher recommends that policies that allow the total usage of all declared official languages in Zimbabwe.